Women’s Family Roles Strengthen Contemporary Islamic Education: Peran Keluarga Perempuan Menguatkan Pendidikan Islam Kontemporer - Siagian, Hairun Nisa; Nahar , Syamsu; Ok, Azizah Hanum (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Women’s roles in Islam are framed through Qur’anic teachings that affirm dignity, rights, responsibility, and participation in family, social, and spiritual life. Specific Background: This study examines women’s roles in family education through Ibn Kathir’s Tafsir al-Qur’an al-‘Azim, especially as wives, mothers, daughters, and educators. Knowledge Gap: Existing discussions on women in Islamic education require a clearer thematic reading of Ibn Kathir’s interpretation and its relevance to contemporary Islamic education. Aims: This study aims to examine Ibn Kathir’s scholarly background, his interpretive approach, women’s roles in family education, and the relevance of these roles to contemporary Islamic education. Results: The findings show that Ibn Kathir applied tafsir bi al-ma’thur with a tahlili approach by interpreting Qur’anic verses through other verses, prophetic traditions, Companions’ views, and Successors’ opinions. His interpretation presents women as wives who foster household harmony, mothers who bear major biological, moral, emotional, and spiritual responsibilities, daughters who contribute responsibly to family life, and educators who guide faith, morality, piety, and character formation. Novelty: The study recontextualizes Ibn Kathir’s classical exegesis by connecting women’s family roles with contemporary Islamic education, gender justice, women’s empowerment, and character formation. Implications: The findings indicate that Ibn Kathir’s interpretation remains relevant for strengthening family-based Islamic education while requiring contextualization to address modern social dynamics and broader roles of women. Highlights• Ibn Kathir presents women as wives, mothers, daughters, and educators.• Mothers hold central responsibility in faith, morality, and character formation.• Classical Qur’anic exegesis remains relevant when contextualized for modern society. KeywordsIbn Kathir; Women Roles; Family Education; Islamic Education; Qur’anic Exegesis